State or public service broadcasting?: an analysis of the coverage of political issues and debates during an election campaign on television news - Macha, Herbert (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2002)
Public Service Television remains a key institution of democratisation in the context of emerging democracies in Africa, especially with the advent of liberalisation and commercialisation of the media. The democratic changes taking place in Zambia require a genuine public service broadcasting television that will promote pluralism in the public sphere. Among the many available strategies and mechanisms for fostering a sustainable democratic and cultural environment, public service broadcasting is still the best. This study set out to examine representation of political issues and debates during election campaign on ZNBC television news to assess the extent to which it plays a role as a public broadcaster in the mediation of pluralistic politics. Election news on television, in line with the public sphere argument was found to be essential for investigating the nature of public service television from the point of view of impartiality, universality and diversity. Using both qualitative and quantitative methods the study has confirmed the hypothesis that the role of a public service television in the mediation of pluralistic politics is compromised by ZNBC's partial and unbalanced coverage of elections. As a result ZNBC, as a public service broadcaster is undermining the very democracy it is expected to promote. Public service television should take new forms if it is to be recognised and appreciated by the public as a genuine, open and democratic public sphere. I therefore recommend that a system of license fee for viewers be introduced. Secondly, government should increase funding into public service television to supplement revenue from license fee and advertising. Thirdly, I recommend the appointment of an independent board whose members will be appointed for a fixed term, by public nomination and a process of public hearing, according to publicly available criteria, which guarantees diversity of political, ethnic, social and professional background. Fourthly I suggest the formation of an Election News Coverage Committee comprising of journalists, academicians, the church and civic organisation that will formulate and implement editorial policy on election coverage and above all monitor and the coverage of elections on ZNBC television news.
Keywords: Public service television programs -- Zambia; Television in politics; Television broadcasting of news -- Zambia; Elections -- Zambia